NILAIâNILAI AJARAN MORAL YANG TERKANDUNG DALAM TEKS SERAT DONGENG CEKRUK TRUNA (SUATU TINJAUAN FILOLOGIS) - Salamah, Rohmatullaili; Widodo, Sisyono Eko; Supardjo, Supardjo (Universitas Muhammadiyah Surakarta, 2012)
This study aims to determine the values of the moral teachings contained in Serat Dongeng Cekruk Truna tales. Data Source was catalogs containing information about the existence of Serat Dongeng Cekruk Truna manuscript. Data were collected by photography and transliteration. Data analysis technique used is techniques of philology referring to the working of philology . Serat Dongeng Cekruk Truna was plural manuscript. Text Edited method was through four stages: ( 1 ) a description of the manuscript ( 2 ) comparison of the manuscript ( 3 ) determination of the basic text ( 4 ) edits the text and apparatus criticism. The descriptive technique was used to describe the issues contained in the fibers tales Cekruk Truna with in-depth analysis. The results of this research can be concluded that the manuscript text Fiber A Tale Cekruk Truna number 221, a collection of Surakarta Literature Foundation, was the most representative and accountable among othres. Serat Dongeng Cekruk Truna tales contain moral teachings expressed symbolically. The moral teachings include: Experience is the best teacher, believing the unity of God and receive His nature, donation in Godâ name and hard, and balancing science study. The teachings can be utilized for youth to advance human resource , especially to education .